2002
DOI: 10.1021/ie010665p
|View full text |Cite
|
Sign up to set email alerts
|

Steam/CO2Reforming of Methane. Carbon Formation and Gasification on Catalysts with Various Potassium Contents

Abstract: A rigorous kinetic model for the formation and gasification of filamentous carbon on a nickel steam-reforming catalyst is derived. Carbon formation and gasification experiments were performed in an electrobalance unit at temperatures ranging from 773 to 823 K and partial pressures of the various components in the range encountered in industrial steam reformers. The rates of growth or gasification of the carbon filaments were always based on the same number of carbon filaments. The gasification by carbon dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…In literature [40], it is mentioned that potassium can migrate from the support to the nickel particles, and be placed, predominantly, on their surface. Recent studies [41] have demonstrated, by DFT calculations that a stepped nickel surface is more active than a surface with close-packed terraces for hydrocarbon reforming reaction and, also, for coke formation.…”
Section: Catalytic Activity Coke Deposition and Characterization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature [40], it is mentioned that potassium can migrate from the support to the nickel particles, and be placed, predominantly, on their surface. Recent studies [41] have demonstrated, by DFT calculations that a stepped nickel surface is more active than a surface with close-packed terraces for hydrocarbon reforming reaction and, also, for coke formation.…”
Section: Catalytic Activity Coke Deposition and Characterization Ofmentioning
confidence: 99%
“…This blockage, however, does not stop the reforming reaction because it can still take place on the unblocked, less active, sites of the nickel surface (close-packed terraces). Snoeck and Froment [40], after their study about the effect of potassium addition to nickel catalyst for CH 4 steam reforming, proposed that the most important effect of potassium is the decrease of the value of the lumped forward rate coefficient for methane craking. This is due to a reduction of the number of sites available for methane decomposition as a consequence of the presence of potassium on the metal surface.…”
Section: Catalytic Activity Coke Deposition and Characterization Ofmentioning
confidence: 99%
“…The major industrial problem observed with the syngas production methods described by Eqs. (1) and (2) is methane cracking, which leads to coke formation over the catalyst and subsequent deactivation of the catalyst [3,4]. In addition, traces of H 2 S in natural gas rapidly poison the catalyst in the reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Another method of syngas production which has been of interest from a research perspective in recent years is catalytic methane reforming by CO 2 , as described by Eq. (3) [5]: CH 4 + CO 2 → 2CO + 2H 2 DH = 247.3 kJ mol -1 (3) This method is useful in the elimination of CO 2 as a greenhouse gas. The reaction described by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…It is claimed that K prevents carbon formation on Ni catalysts by blocking step sites which are believed to be the nucleation sites for graphite formation [50]. In addition, potassium on Ni catalysts enhances coke gasification [51]. It was reported by Dicks et al [37] that small amounts of potassium reduce the risk of carbon deposition by decreasing the acidity of the catalyst support.…”
Section: Catalyst Deactivationmentioning
confidence: 99%